Exploring the relationship between activity cost and aroma loss of Hom Mali rice during post-harvest stage - Lilavanichakul, Apichaya; Parthanadee, Parthana; Wiratchai, Aueamorn (Kasetsart Journal of Social Sciences, 2021)
Hom Mali rice contains various unique characteristics with one being its aroma. A reduction in the aroma or 2-acetyl-1-pyrroline (2AP) of Hom Mali rice during post-harvesting activities has become a major problem for stakeholders and exporters in the rice supply chain. This paper investigated logistics and processing cost analysis of the rice mills of two agricultural cooperatives, AC1 and AC2, by using the activitybased costing (ABC) method. Moreover, the relationship between the loss of aroma and the cost processing activity has been explored using partial correlation. Findings showed that the total cost of AC1 was 4.986 baht/kg, which was separated into the logistics cost of 58.18 percent and the processing cost of 41.82 percent. The total cost of AC2 was 5.851 baht/kg, consisting of the logistics cost of 77.34 percent and the processing cost of 22.66 percent. For the processing activities, the significant relationship between the activity costs and the loss of aroma, while controlling the levels of 2AP, suggested that aroma retaining must regard decisions on the selections of processing activities including polishing, whitening, bagging, and dehulling activities. In the logistics aspect, the cooperatives should focus on raw material receiving, warehousing, packing, and transportation activities. Decisions on the improvement of logistics and processing activities involved with aroma loss of Hom Mali rice should rely on cost analysis, maintaining the quality of rice, and meeting both domestic and international demand.